The Relationship Between Access to Health Services and Service Quality in Realizing a Just and Sustainable Health System - Yusnaini Yusnaini; Nandara Priyanti Elna; Mira Novita (Sean Institute, 2026)
Access to healthcare services is an important determinant in improving the quality of healthcare services, particularly in rural areas that still face geographical and digital limitations. Inequality in access has the potential to hinder the realization of an equitable and sustainable healthcare system. This study aims to analyze the relationship between access to healthcare services and the quality of healthcare services. The research employed a descriptive analytic correlational design with a cross-sectional approach. The sample consisted of 150 community respondents in rural areas of Southeast Aceh Regency selected through purposive sampling. Data were collected using a structured questionnaire measuring dimensions of access (availability, affordability, acceptability, and digital access) as well as the quality of healthcare services. Data analysis was conducted bivariately using statistical tests appropriate to the level of data measurement. The results showed that most respondents perceived access to healthcare services as still inadequate, particularly in terms of geographical affordability and digital access. The quality of healthcare services was categorized as fairly good, although weaknesses remained in infrastructure and facilities. Bivariate analysis indicated a significant relationship between access to healthcare services and the quality of healthcare services (ρ-value < 0.05). Therefore, it is expected that efforts will be made to improve access to healthcare services through strengthening infrastructure, equitable distribution of healthcare personnel, and optimization of digital-based services to support the realization of a fair and sustainable healthcare system.